Light-shift suppression in laser optically pumped vapour-cell atomic frequency standards - Affolderbach, Christoph; Andreeva, C.; Cartaleva, S.; Karaulanov, T.; Mileti, Gaetano; Slavov, D (My University, 2005)
We present a novel scheme for reducing the AC Stark effect in optical-microwave double-resonance spectroscopy and its application for efficient suppression of the light-shift-related instabilities in laser-pumped gas-cell atomic clocks. The method uses a multi-frequency pump light field that can be easily produced by frequency modulation of the single-frequency pump laser. We show theoretically that variations of the light shift with both laser frequency and light intensity can be strongly suppressed with properly chosen pump light spectra. Suitable modulation parameters can be found for both the case of pure frequency modulation as well as for pump light spectra showing amplitude-modulation contributions, as usually found for current modulation of diode lasers. We experimentally demonstrate the method for a Rb atomic clock using a frequency-modulated distributed Bragg-reflector laser diode as pump light source.